2020
DOI: 10.3390/biomedicines8020030
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Statin Use on Dementia Incidence in Elderly Men and Women with Ischemic Heart Disease

Abstract: This study aimed to determine the association between statins and the prevention of dementia according to sex differences in elderly patients with ischemic heart disease (IHD). We performed a nationwide retrospective cohort study using the Korean Health Insurance Review and Assessment Service database (2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015). Among the 264,036 eligible patients aged ≥65 years with IHD, statin users were compared with non-users by propensity score matching at a 1:1 ratio (71,587 i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 52 publications
0
20
0
Order By: Relevance
“…More specifically, in mouse models of AD, the use of statin lowered hippocampal Aβ levels and improved cognitive awareness (82). Clinically, studies have reported that the use of statin is associated with lower risk of dementia in elderly populations (83). In animal models of PD, statins attenuated dopamine depletion, enhanced BDNF production, and decreased neuroinflammatory markers such as TNFα and Il‐1β.…”
Section: Mets Pharmacotherapy and Neurodegenerative Diseasementioning
confidence: 99%
“…More specifically, in mouse models of AD, the use of statin lowered hippocampal Aβ levels and improved cognitive awareness (82). Clinically, studies have reported that the use of statin is associated with lower risk of dementia in elderly populations (83). In animal models of PD, statins attenuated dopamine depletion, enhanced BDNF production, and decreased neuroinflammatory markers such as TNFα and Il‐1β.…”
Section: Mets Pharmacotherapy and Neurodegenerative Diseasementioning
confidence: 99%
“…In the age subgroup of 75-85, atorvastatin and rosuvastatin use was associated with reduced AD risk. However, no significant association was found in the age subgroup of 86 and older, which could be explained by the lower sample size in this subgroup (Kim et al, 2020). Yet, a recent study has found that the association between statin therapy and cognitive function is not modified by age (Roy et al, 2020).…”
Section: Agementioning
confidence: 74%
“…Major reduction in the dementia risk (Poly et al, 2020). Reduction of dementia risk only in men with IHD (Kim et al, 2020). Preclinical meta-analysis showed the maximum reduction of Aβ plaques (Rahman et al, 2020).…”
Section: Statins Solubility Statins Type Effects On Cognitive Functionmentioning
confidence: 95%
“…Statins, which are used to treat hyperlipidemia, may delay progression to AD 96 ; rosuvastatin was associated with a decreased risk of dementia among patients with ischemic heart disease. 97 However, it has also been suggested that statins may be associated with dementia; so, further research is needed. 98 Observational data for blood pressure control suggest that the window of highest benefit for the treatment of hypertension is in midlife, and that overaggressive control of hypertension in the elderly is associated with cognitive decline and dementia, possibly due to hypoperfusion from hypotension.…”
Section: Prevention Of Cognitive Decline In the Cardiac Patientmentioning
confidence: 99%